Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.